EMPLOYEE PERFORMANCE BASED ON MOTIVATION AND WORK ENVIRONMENT - Dwi Gemina; Samsuri Samsuri; Livia Amertiana Khoirunisa; Sri Harini; Palahudin Palahudin (Bajang Institute, 2023)
Performance is an important factor to measure the results of employee work so that the achievement of company goals in productivity is also measured. This study aims to determine and analyze the effect of motivation and work environment on the performance of employees of PT Honoris Industry Bogor. This research design uses descriptive and verification methods. The sampling technique in this study used a type of probability sampling with simple random sampling technique. The number of respondents was 100 people. The subjects of this research are employees of PT Honoris Industry Bogor, and the objects of this research are motivation, work environment and employee performance. The tools used in this analysis are path analysis, multiple correlation analysis, coefficient of determination analysis and hypothesis testing with the F test and T test. The results showed that employee responses to motivation variables were in the high category, the work environment was in the very good category and employee performance was in the high category. Motivation and work environment have a direct and positive effect on the performance of employees of PT Honoris Industry Bogor. Motivation has a direct and positive effect on the performance of employees of PT. Honoris Industry Bogor. The work environment has a direct and positive effect on the performance of employees of PT. Honoris Industry Bogor